2007
DOI: 10.1111/j.1365-2966.2007.12044.x
|View full text |Cite
|
Sign up to set email alerts
|

The SCUBA HAlf Degree Extragalactic Survey - III. Identification of radio and mid-infrared counterparts to submillimetre galaxies

Abstract: Determining an accurate position for a submillimetre (submm) galaxy (SMG) is the crucial step that enables us to move from the basic properties of an SMG sample – source counts and 2D clustering – to an assessment of their detailed, multiwavelength properties, their contribution to the history of cosmic star formation and their links with present‐day galaxy populations. In this paper, we identify robust radio and/or infrared (IR) counterparts, and hence accurate positions, for over two‐thirds of the SCUBA HAlf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
315
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 285 publications
(349 citation statements)
references
References 107 publications
33
315
1
Order By: Relevance
“…A matching radius of 1 was adopted (85% of matches are found within 0 5) to account for both the formal uncertainty on the ALMA positions (σ ∼ 0 14 for a 4σ detection; see Ivison et al 2007) and any intrinsic spatial offset resulting from dust obscuration (σ ∼ 0. 3  , with offsets of up to 2 to individual components; Chen et al 2015).…”
Section: Optical and Near-infrared Photometrymentioning
confidence: 99%
See 2 more Smart Citations
“…A matching radius of 1 was adopted (85% of matches are found within 0 5) to account for both the formal uncertainty on the ALMA positions (σ ∼ 0 14 for a 4σ detection; see Ivison et al 2007) and any intrinsic spatial offset resulting from dust obscuration (σ ∼ 0. 3  , with offsets of up to 2 to individual components; Chen et al 2015).…”
Section: Optical and Near-infrared Photometrymentioning
confidence: 99%
“…Thus, a possible explanation for the higher median redshift of the SMGs presented here, relative to ALESS, is that brighter SMGs are preferentially found at higher redshift. Indeed, a number of authors previously suggested that 870 μm brighter sources may lie at higher redshift (e.g., Ivison et al 2002Ivison et al , 2007Koprowski et al 2014).…”
Section: Photometric Redshift Distribution Of Smgsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has the potential to bias the redshift distribution to z 3.5  , especially if a significant fraction of submillimeter sources do not have multi-wavelength counterparts. Indeed, in single-dish 850 μmsurveys, up to 50% of all submillimeter sources are undetected at radio wavelengths (e.g., Ivison et al 2005Ivison et al , 2007Biggs et al 2011). Some progress can be made by targeting lensed sources whose multi-wavelength identifications are less ambiguous, and indeed spectroscopic redshifts have been derived for SMGs up to z 5 (e.g., Weiß et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…• 00 ′ 00 ′′ ) is one of two regions in SHADES where number count (Coppin et al 2006), redshift distribution (Aretxaga et al 2007;Ivison et al 2007;Clements et al 2008) and physical parameters of SMGs (Clements et al 2008) were investigated. In this study, we also investigate number count and physical properties of SMGs in blank-field using 850 µm imaging data centered at (α 2000 , δ 2000 ) = (02 h 18 m 07 s , -04…”
Section: Corresponding Author: H Seomentioning
confidence: 99%